Factors influencing platelet count increment after platelet transfusion among thrombocytopenic patients in Hospital USM - Hayat, Mohd Zamri Mohd (2016)
Many studies had been performed to determine the factors that may contribute to posttransfusion platelet increment. However, no documented data is available in our institution in this area of knowledge yet. Therefore, this study was conducted to determine the transfusionrelated factors that may influence post-transfusion platelet increment in thrombocytopenic patients. This retrospective cohort study involved 97 patients who received 351 of platelet transfusions in Hospital Universiti Sains Malaysia within the period of January 2013 till December 2014. The pre and post transfusion platelet counts were measured by using Sysmex haematology analyzer XE5000 and the corrected count increment (CCI) was calculated at 1 hour and 24 hours post transfusion. Poor increment was defined as CCI<7500 m2/L at 1 hour and CCI<4500 m2/L at 24 hours. The analyzed factors included, underlying malignancy, fever, DIC, bleeding, splenomegaly, type of platelet concentrates (random versus apheresis), ABO compatibility and age of platelet concentrates. Simple (SLR) and multiple logistic regression (MLR) were used for statistical analysis and p-value of < 0.05 considered as significant. Most patients were Malays (92.8%) with a median age of 47 years old. Male and female patients were nearly equal in number. Majority of patients were O positive (40.2%) followed by B positive (27.8%), A positive (26.8%) and AB positive (5.2%). The mean and median ofCCI was 15,834.54 m2/L and 10,350m2/L, respectively. The proportion patients with good CCI was 66.1%. SLR and MLR showed that only DIC, platelet age and ABO compatibility were significant factors influencing post-transfusion platelet increment. DIC had 5.31 and 4.41 time adjusted odds for poor post-transfusion platelet CCI (p-value<0.001, 95%CI=3.06,9.24) and platelet refractoriness (p- value <0.001,95%CI=2.0,9.7), respectively. Meanwhile, platelet age of >3 days had 2.2 time adjusted odds of poor CCI compared to fresh platelet (p-value = 0.004, 95% CI=1.29,3.75). ABO compatible platelet transfusion had 80% adjusted odds of unlikelihood to get poor post-transfusion CCI compared with ABO identical platelet (p-value=0.011, 95%CI=0.06,0.65). Other clinical and laboratory factors were not statistically significant. In conclusion, patients with DIC and who receive day ≥4 platelet concentrates will need more platelet transfusions to achieve the desirable platelet increment compared to non DIC patients and who receiving day ≤3 platelet concentrates patients, respectively. In addition, patients who receive ABO compatible platelet concentrates may need fewer platelet transfusion than ABO identical in achieving the similar target platelet level.